Pencegahan Dan Perlindungan Hukum Terhadap Kriminalisasi Jabatan Notaris - Valentino, Finanto; Dahana, Cokorda Dalem (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 7 No 02 (2022)DO - 10.24843/AC.2022.v07.i02.p13, 2022)
This research was conducted with the aim of knowing preventive measures and also legal protection for notaries in terms of criminalization and also knowing the return of rights and conditions for notaries who were proven innocent. This research uses a normative juridical research method, with a focus on legal norms and existing rules. And based on these problems, two problems were drawn and the results were obtained: (1) that the notary in carrying out his position, especially in making authentic deeds, in addition to referring to the UUJN and the notary code of ethics, in terms of reducing the risk of errors, must also apply the precautionary principle, so that can minimize the occurrence of disputes related to the deed he made even though there is already a legal presumption that protects. (2) Detention of a notary if it is indicated that a crime related to an authentic deed he made will certainly cause a lot of harm to the notary, because it is necessary to restore the rights and conditions of a proven Notary not guilty but prior detention in UUJN is not regulated in this regard, but can be found in the general provisions of the Criminal Procedure Code at point 3 (d) related to compensation and rehabilitation.